2001
DOI: 10.1021/bi0113723
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution and Analysis of the Chain Initiating Enzymes of the R1128 Polyketide Synthase

Abstract: Biosynthesis of the carbon chain backbone of the R1128 substances is believed to involve the activity of a ketosynthase/chain length factor (ZhuB/ZhuA), an additional ketosynthase (ZhuH), an acyl transferase (ZhuC), and two acyl carrier proteins (ACPs; ZhuG and ZhuN). A subset of these proteins initiate chain synthesis via decarboxylative condensation between an acetyl-, propionyl-, isobutyryl-, or butyryl-CoA derived primer unit and a malonyl-CoA derived extender unit to yield an acetoacetyl-, beta-ketopentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 18 publications
(36 reference statements)
3
62
0
Order By: Relevance
“…We previously showed that nonacetate-primed aromatic PKSs contain discrete initiation modules that typically consist of (i) a second ACP (ACP p ) that primes the minimal PKS with the nonacetate unit (34), (ii) a ketosynthase III that synthesizes the ACP p -bound primer unit (39), and (iii) a potent acetyl-ACP thiolase that hydrolyzes the competing acetyl-ACP species that may otherwise initiate polyketide assembly with acetate (56). An ORF (oxyP) 15 kb downstream of the minimal PKS genes encodes an enzyme of high sequence homology to acetyl-ACP thiolases, such as ZhuC from the R1128 PKS (34) (49% identity) and FrnK from the frenolicin PKS (1) (43% identity).…”
Section: Sequencing Of Oxytetracycline Gene Clustermentioning
confidence: 99%
“…We previously showed that nonacetate-primed aromatic PKSs contain discrete initiation modules that typically consist of (i) a second ACP (ACP p ) that primes the minimal PKS with the nonacetate unit (34), (ii) a ketosynthase III that synthesizes the ACP p -bound primer unit (39), and (iii) a potent acetyl-ACP thiolase that hydrolyzes the competing acetyl-ACP species that may otherwise initiate polyketide assembly with acetate (56). An ORF (oxyP) 15 kb downstream of the minimal PKS genes encodes an enzyme of high sequence homology to acetyl-ACP thiolases, such as ZhuC from the R1128 PKS (34) (49% identity) and FrnK from the frenolicin PKS (1) (43% identity).…”
Section: Sequencing Of Oxytetracycline Gene Clustermentioning
confidence: 99%
“…(Figure 3) 12,19,20,21 In some cases, such as the R1128 PKS and the daunorubicin PKS, the synthase includes a dedicated module of enzymes for chain initiation. 22,23 Recent studies have demonstrated that these initiation modules can collaborate with elongation modules from heterologous octaketide synthases and decaketide synthases to produce non-acetyl primed hexaketide and octaketide natural products, respectively. 24 In each case, chain length of the polyketide backbone is dictated by the elongation module (i.e., the minimal PKS).…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated first by Khosla and co-workers (44), the oxy minimal PKS alone synthesizes exclusively acetateprimed decaketides. In other pathways in which nonacetate starter units are employed, such as daunorubicin (45), frenolicin (46), R1128 (46,47), and hedamycin (48,49), an additional initiation module has been implicated in starter unit selection. In the case of frenolicin and R1128, it was further shown that a dedicated ACP is required for the chain initiation steps and plays a different role than the ACP utilized by the minimal PKS for chain elongation (46).…”
Section: Biosynthesis Of the Amidated Polyketide Backbonementioning
confidence: 99%